Scientist trust in medical research: a survey of authors from 28 countries - Mainous, Arch G.; Kellie, J. A.; Liu-Galvin, Rachel E.; Durden, Barbara; Beau de Rochars, Valery M. (Frontiers in Medicine, 2025)
ImportancePeer-review is the lynchpin to research integrity, quality and trust in published health research findings.ObjectiveTo evaluate the level of trust in peer-reviewed and non-peer-reviewed medical research among scientists who publish medical research.MethodsA survey was conducted of corresponding authors of papers accepted for publication in a peer-reviewed medical journal between September and December 2024 (n = 285). Survey questions focused on trust in the results in peer-review and non-peer-reviewed results. Deidentified data was provided to the current investigators for a secondary analysis. The level of press freedom in the country and whether the investigators in the country were oriented toward scientific papermills for publishing research was also evaluated.ResultsAlthough 94% of the respondents have high trust in peer-reviewed research, a significant proportion (32.4%) have trust in non-peer-reviewed research. A majority (54.7%) believe that public trust in medical research findings is influenced by the reader’s political beliefs. The current peer review system is too slow (79%). Respondents from countries with a high prevalence of use of scientific papermills and low press freedom had more agreement that non-peer-reviewed research should be indexed than those from other countries (both p < 0.01). Authors who have published few papers are more trusting of non-peer-reviewed research (p.006) and more in agreement that non-peer-reviewed research should be indexed (p.015).ConclusionRebuilding the guardrails and trust in peer-review is necessary. A more streamlined peer-review system may be necessary to rebuild trust.